Without the inclusion of an equality sign the expression can not be considered to be an equation
The mathematical phrase "6x" is not an equation. It is simply an expression. In math, an expression is a term or terms like 5 or 3x + 2. An equation must show an expression's relationship to another: 5x + 3 = 4 3 + 2 = 5
The equation x = 3 has a solution of x = 3. This is because when you substitute x = 3 into the equation x = 3, it satisfies the equation and makes it true. Therefore, x = 3 is the equation with the solution x = 3.
If: 6x-4+7 = 5 Then: x = 1/3
If you mean: 4x+3 = 6x-9 then the value of x works out as 6
If the square root of 6x-2=4 than we can square both sides and we have 6x-2=16 or 6x=18 and the solution set is the set that contains the number 3.
If 6x - 3 = -51, then x = -8
Without an equality sign the given expression is not an equation and so therefore a solution is not possible.
6X-3 = -51 add 3 to both sides 6X = -48 divide by 6 X = -8
6x - 12 = 16 is a linear equation in one variable(here x). And the value of x which satisfies the equation is the solution. Let us find the value of x: 6x - 12 = 16 Adding 12 to both sides, we get 6x - 12 + 12 = 16 + 12 6x = 28 Dividing both sides by 6, we get x = 28/6 = 14/3 So, the solution of the equation is x = 14/3.
The result of the equation 6x -3 less than 3 is X < 1.
If you mean: y = 6x-4 then the parallel equation is y = 6x+10
It is exactly as in the question: y = -6x + 3
This system is inconsistent. There is no solution. 2x - 3y = 5 -6x + 9y = 12 Multiply the top equation by 3: 6x - 9y = 15 add the two equations together: 6x - 6x - 9y + 9y = 5 + 12 0 = 17 Which is a contradiction. Therefore the lines never intersect, and the solution is the empty set.
From what i understand the equation is like this; (3 * 2 ) + 6x + 24 = 0 6 + 6x +24 = 0 6x = - 24 - 6 6x = - 30 x = - 5
You'll need another equation to solve this one. The equation you give has a graph that is a line. Every point on the line is a solution to the equation so there are infinitely many solutions.
-3x2 = 5 + 3x (add 3x2 to both sides)0 = 3x2 + 5 + 3x or3x2 + 3x + 5 = 0 (since the discriminant is less than zero, we have complex roots)x = [-3 ± √[(32 - 4(3)(5)]]/2(3)x = [-3 ± √(9 - 60)]/6x = (-3 ± √-51)/6x = (-3 ± i√51)/6x = (-3 + i√51)/6 = -1/2 + (√51/6)i orx = (-3 - i√51)/6 = -1/2 - (√51/6)i
-3